Hiperactividad en los niños y niñas - Peñaherrera Murillo, Jonathan Anibal (2016)
The present research is to develop workshops on basic education school Azuay that allow teachers to learn about hyperactivity and provide adequate attention to students who exhibit these factors in the educational community, the social interaction between them is very important since that verbal, emotional and academic connection depends on the positive development of the student's educational role, they have different responsibilities behavior within the teaching-learning process. The inquiry will focus directly to students, verifying their ways of behavior to identify their hyperactivity its presence and impact in the classroom; it is important to note that it is not something that only affects the educational area of the child but also the family and social environment. It is important that teachers and parents to learn different strategies to act against the problem as it will bring benefits associated with early warning techniques of behavior, because this disorder is diagnosed more frequently in children / as, therefore be assessed symptoms embedded into different groups such as: not being able to concentrate (neglect or inattention), be extremely active and not being able to control the behavior; therefore it states that educational institutions pay more attention to students who present this disturbance can improve and go changing their behavior at home and at school and prevent academic failure or definitively withdrawn from the educational establishment is It proposed by the inquiry for that institution to acquire a better knowledge on the subject which will help students to recognize the type of behavior to improve their academic performance and try to correct and that the educational community know how to identify the specific characteristics of the difficulty.